Isolation of Induced Morphological Mutants in Capsicum annuum L. - J. E. Thoppil, C. M. Abdul Salam, (Journal of Phytology, 2010)
Seeds of Capsicum annuum L. varieties Co – 1 and Ujwala were treated with two chemical mutagens viz., Ehtyl methane sulphonate and Sodium azide. Twelve different types of morphological mutants were isolated in M2 and M3 generations. Capsaicin content of some selected mutants was also estimated. Frequency of morphological mutants obtained was very high in variety Co -1 when compared to Ujwala.